2021
DOI: 10.3390/nano11113160
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulations on Metal Rod Penetrating Thin Target at Nanoscale Caused by High-Speed Collision

Abstract: The penetration process has attracted increasing attention due to its engineering and scientific value. In this work, we investigate the deformation and damage mechanism about the nanoscale penetration of single-crystal aluminum nanorod with atomistic simulations, where distinct draw ratio (∅) and different incident velocities (up) are considered. The micro deformation processes of no penetration state (within 2 km/s) and complete penetration (above 3 km/s) are both revealed. The high-speed bullet can cause hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Besides nanomaterials, plenty of works have investigated the atomistic underlying mechanisms for the mechanical behaviors of engineering materials, which provides useful guidelines for the design of high-performance materials. For example, Wu et al [ 34 ] probed the penetration process of aluminum nanorod through atomistic simulations, and Wan et al [ 35 ] assessed how the initial void influence the damage characteristic of single crystal aluminum under shock loading. Interestingly, Jiang et al [ 36 ] found that the presence of copper nanoparticle will trigger the formation of regular stacking fault in the single crystal aluminum under shock compression.…”
mentioning
confidence: 99%
“…Besides nanomaterials, plenty of works have investigated the atomistic underlying mechanisms for the mechanical behaviors of engineering materials, which provides useful guidelines for the design of high-performance materials. For example, Wu et al [ 34 ] probed the penetration process of aluminum nanorod through atomistic simulations, and Wan et al [ 35 ] assessed how the initial void influence the damage characteristic of single crystal aluminum under shock loading. Interestingly, Jiang et al [ 36 ] found that the presence of copper nanoparticle will trigger the formation of regular stacking fault in the single crystal aluminum under shock compression.…”
mentioning
confidence: 99%